Feasibility of His‐bundle pacing in patients with conduction disorders following transcatheter aortic valve replacement. (5th February 2020) - De Pooter, Jan; Gauthey, Anaïs; Calle, Simon; Noel, Antoine; Kefer, Joelle; Marchandise, Sebastien; Coeman, Mathieu; Philipsen, Tine; Kayaert, Peter; Gheeraert, Peter; Jordaens, Luc; Timmermans, Frank; et al.
Abstract: Background: Conduction disorders requiring permanent pacemaker implantation occur frequently after transcatheter aortic valve replacement (TAVR). This multicenter study explored the feasibility and safety of His bundle pacing (HBP) in TAVR patients with a pacemaker indication to correct a TAVR‐induced left bundle branch block (LBBB). Methods: Patients qualifying for a permanent pacemaker implant after TAVR were planned for HBP implant. HBP was performed using the Select Secure (3830; Medtronic) pacing lead, delivered through a fixed curve or deflectable sheath (C315HIS or C304; Medtronic). Successful HBP was defined as selective or nonselective HBP, irrespective of LBB recruitment. Successful LBBB correction was defined as selective or nonselective HBP resulting in paced QRS morphology similar to pre‐TAVR QRS and paced QRS duration (QRSd) less than 120 milliseconds with thresholds less than 3.0 V at 1.0‐millisecond pulse width. Results: The study enrolled 16 patients requiring a permanent pacemaker after TAVR (age 85 ± 4 years, 31% female, all LBBB; QRSd: 161 ± 14 milliseconds). Capture of the His bundle was achieved in 13 of 16 (81%) patients. HBP with LBBB correction was achieved in 11 of 16 (69%) and QRSd narrowed from 162 ± 14 to 99 ± 13 milliseconds and 134 ± 7 milliseconds during S‐HBP and NS‐HBP, respectively ( P = .005). At implantation, mean threshold for LBBB correction was 1.9 ± 1.1 V at 1.0 millisecond. Thresholds remained stable at 11 ± 4 months follow‐up (1.8 ± 0.9 V at 1.0 millisecond, P = .231 for comparison with implant thresholds). During HBP implant, one temporary complete atrioventricular block occurred. Conclusion: Permanent HBP is feasible in the majority of patients with TAVR requiring a permanent pacemaker with the potential to correct a TAVR‐induced LBBB with acceptable pacing thresholds.